Safety in solitude? Competing risks and drivers of solitary drug use among women who inject drugs and implications for overdose detection. - Rosen, Joseph G.; Glick, Jennifer L.; Zhang, Leanne; Cooper, Lyra; Olatunde, Praise F.; Pelaez, Danielle; Rouhani, Saba; Sue, Kimberly L.; Park, Ju Nyeong (Addiction, 2023)
Background and aims: Solitary drug use (SDU) can amplify risks of fatal overdose. We examined competing risks and drivers of SDU, as well as harm reduction strategies implemented during SDU episodes, among women who inject drugs (WWID). Design: A cross‐sectional qualitative study, including telephone and face‐to‐face in‐depth interviews. Setting: Baltimore City, MD, USA. Participants: Twenty‐seven WWID (mean age = 39 years, 67% white, 74% injected drugs daily) recruited via outreach and street intercept (April–September 2021). Measurements Interviews explored the physical (i.e. indoor/private, outdoor/public) and social (i.e. alone, accompanied) risk environments in which drug use occurred. Guided by the principles of emergent design, we used thematic analysis to interrogate textual data, illuminating women's preferences/motivations for SDU and strategies for minimizing overdose risks when using alone. Findings Many participants reported experiences with SDU, despite expressed preferences for accompanied drug use. SDU motivations clustered around three primary drivers: (1) avoiding opioid withdrawal, (2) preferences for privacy when using drugs and (3) safety concerns, including threats of violence. Participants nevertheless acknowledged the dangers of SDU and, at times, took steps to mitigate overdose risk, including naloxone possession, communicating to peers when using alone ('spotting') and using drugs in public spaces. Conclusions: WWID appear to engage frequently in SDU due to constraints of the physical and social environments in which they use drugs. They express a preference for accompanied drug use in most cases and report implementing strategies to mitigate their overdose risk, especially when using drugs alone.